Impact of processing on the stability and bioaccessibility of Pro-Vitamin A Carotenoids in biofortified cassava roots (Manihot esculanta, Crantz) - Aragón Gallego, Ingrid J.; Dufour, D.L.; Escobar Salamanca, Andrés F.; Calle, Fernando; Ferruzzi, Mario G. (2016)
Carotenoid content in cassava roots has been increased through biofortification programs as a strategy to combat vitamin A deficiency. However, incorporation of biofortified cassava into both traditional and industrial food processing has yet to be fully assessed. The objective of this study was to examine the impact of fermentation and thermal processing on the stability and bioaccessibility of pro-vitamin A carotenoids from distinct biofortified cassava roots. Unfermented (UF) and fermented (F) flours were produced from 10 biofortified cassava cultivars (Table 1 & Figure 2). Gari (G) flours were produced by toasting two of the fermented cultivars above at 150-160oC during 15-20 min. Test porridges were prepared with UF, F and G (22.2% W/V) in boiling water for 5 min. Bioaccessibility of pro-vitamin A carotenoids was then evaluated from finished products using a three-stage in vitro digestion model (Figure 3). Overall, cassava cultivars contained 23.1-42.7 μg of β-carotene equivalents (β-CE) / g on dry weight bases (DW). β-CE retention after fermentation was 72.5-96.6%; after oven-drying were 18.3-77.5% and 45.8-80.4% for UF and F roots, respectively; after toasting in Gari preparation was 67.3-69.2%; after cooking in porridge preparations were 42.5-74.5%, 20.7-77.3% and 87.2-115.3% for UF, F and G flours, respectively (Figure 4 & 5). Cassava flours, which involved fermentation showed higher β-CE retention (p=0.007) during oven-drying compared with UF flours. However, no significant differences were found in β-CE retention during porridge preparation (p=0.905). Test porridges made from UF, F and G flours ranged from 39-309, 58-343 and 223-323 μg β-CE / 100 g FW, respectively. Bioaccessibility ranged widely from 3.3-56.9 μg β-CE / 100 g FW with bioaccessible content among the cultivars within the porridges groups ranging from 3.3-43.4, 3.66-21.4 and 20.3-56.9 μg / 100 g FW for UF, F and G flours, respectively (Figure 6). In general, bioaccessible β-CE content from porridges prepared with UF and F flours were similar with levels of 14.5 +/- 4.2 and 12.7 +/- 1.8 μg / 100 g FW, (p = 0.700). Select cassava cultivars showed improved bioaccessibility of β- CE content with the fermentation process, these results suggest that genotype factor and/or another factors in the matrix merit further investigation as they may play a significant role in facilitating bioaccessibility of carotenoids from biofortified cassava products.